Experimental Study on the Propagation Characteristics of Hydraulic Fracture in Clayey-Silt Sediments. (14th August 2021) - Lu, Cheng; Qin, Xuwen; Mao, Wenjing; Ma, Chao; Geng, Lantao; Yu, Lu; Bian, Hang; Meng, Fanle; Qi, Rongrong
Abstract : The low permeability of clayey-silt hydrate reservoirs in the South China Sea affects the thermal and pressure conductivity of the reservoir, which is difficult to spread to the far end of the wellbore and achieve commercial gas production. In this respect, enhancing the permeability to assist depressurization is necessary. Hydraulic fracturing is a promising reservoir stimulation method for gas hydrate reservoirs. Up to now, majorities of research focus on the fracability of hydrate-bearing sandy sediments, but the studies rarely involved fracture propagation characteristics of clayey-silt sediments in the hydrate dissociation area. In this paper, three sets of hydraulic fracturing experiments under different confining pressure were carried out using the clayey-silt sediments in the Shenhu Area. Computed tomographic (CT) images indicated that clayey-silt sediments could be artificially fractured, and the fracturing fluid could induce tensile fractures and local shear fractures. A multimorphological fracture zone occurred near the borehole. Furthermore, the greater the confining pressure imposed, the greater the breakdown pressure was, and the microfracture arose more easily. The fractures at the top were generally wider than those at the bottom with the same confining pressure. The experimental results could reveal the fracture initiation and propagation mechanism of clayey-silt sediments and provide theoretical support for hydraulic fracture in the hydrate dissociation area.